21 PHOSPHORYLATION OF b-CATENIN BY PROTEIN KINASE A IN VASCULAR SMOOTH MUSCLE CELLS. (1st March 2006) - Taurin, S.; Sandbo, N.; Qin, Y.; Dulin, N. O.
Abstract : Beta-catenin is a transcriptional coactivator that promotes cell proliferation by induction of genes such as cyclin D1, c-myc, and others. Enhanced b-catenin signaling was observed in many cancer cells and in vascular smooth muscle cells (VSMC) during restenosis. The canonical mechanism of regulation of b-catenin involves its phosphorylation by glycogen synthase kinase 3 (GSK3) that targets b-catenin to ubiquitination and degradation by the proteasome system. Mitogenic factors promote b-catenin signaling through inhibition of GSK3, resulting in reduced b-catenin phosphorylation, its stabilization, and subsequent accumulation in the nucleus, where it stimulates gene transcription. In the present study, we investigated the mechanism of VSMC proliferation induced by extracellular ATP (a VSMC mitogen relevant to the pathogenesis of atherosclerosis and restenosis). We found that (1) ATP potently induces the cyclin D1 transcription in VSMC; (2) stimulation of cyclin D1 transcription by ATP is dependent on b-catenin signaling and on protein kinase A (PKA) activity; (3) b-catenin is phosphorylated by PKA in vitro and in intact cells at two novel sites, Ser-552 and Ser-675; (4) phosphorylation by PKA promotes the transcriptional activity of b-catenin; (v) mutation of Ser-675 attenuates the promoting effect of PKA; (6) phosphorylation by PKA does not affect the GSK3-dependent phosphorylation of b-catenin, its stability or intracellular localization; but (7) phosphorylation at Ser-675 site promotes the binding of b-catenin to its transcriptional coactivator, CREB-binding protein (CBP). In conclusion, this study identifies a novel, noncanonical mechanism of modulation of b-catenin signaling through direct phosphorylation of b-catenin by PKA, promoting its interaction with CBP.